PENGARUH PENAMBAHAN JENIS DAN KONSENTRASI PLASTICIZER TERHADAP KUALITAS BIOPLASTIK BERBASIS SELULOSA DARI TANDAN KOSONG KELAPA SAWIT - Cindy Andahera; Isni Sholikhah; Deah Ayu Islamiati; Memik Dian Pusfitasari (Indonesian Journal of Pure and Applied Chemistry, 2019)
Plastic is a material that commonly used in daily activities. The increasing of using plastic can increase the amount of plastic waste that can give a negative impact on environment. One effort to solve the problem is by replacing plastic material with a material that convenient degraded by soil, that’s called bioplastic. Bioplastic has a biodegradable characteristic and it is 67% compostable. One of the raw material to producing bioplastic is cellulose. Cellulose can be found in non-food plants such as woods, because most of them contain 40-45% cellulose. Oil palm is the one of the plants which is the cellulose taken by utilize oil palm empty fruit bunch. On the other hand, plasticizer must be added for producing bioplastic to make plastic has elastic characteristic. Sorbitol, Glycerol, Oleic Acid are types of plasticizer. In this research, bioplastic is producing by using solution casting method by addition of plasticizer. With these methods indicates that by using sorbitol as plasticizer is more suitable than glycerol and oleic acid. By using 30% v/v sorbitol can get the optimum quality of bioplastic with 58,7% mass reduction using degradation-analysis during 4 days, and maximum attraction which can be detained is 6,27 kPa